Grapheme-color Synesthesia and PTSD: Preliminary Results from the Veterans Health Study - Hoffman, Stuart N. (2012)
OBJECTIVE: Posttraumatic stress disorder (PTSD) is associated with altered neuropsychological function, possibly including complex visual information processing. Grapheme-color synesthesia refers to the phenomenon that a particular letter or number elicits the visual perception of a specific color. The study objective was to assess if grapheme-color synesthesia was associated with PTSD among US veterans. METHOD: We surveyed 700 veterans who were outpatients in a multi-hospital system in Pennsylvania. All veterans had served at least one warzone deployment. PTSD and grapheme-color synesthesia were assessed using a validated research instruments. RESULTS: The mean age of veterans was 59 and 96% were men. The prevalence of current PTSD was 7% (95% C.I. = 5.1–8.8) and current partial PTSD was 11% (95% C.I. = 9.3–14.0). The prevalence of current depression was 6% (95% C.I. = 4.7–8.3). Altogether, 6% (95% C.I. = 4.8–8.5) of veterans screened positive for grapheme-color synesthesia. Bivariate analyses suggested that grapheme-color synesthesia was associated with current PTSD (odds ratio [OR] = 3.4, p = 0.004) and current partial PTSD (OR = 2.4, p = 0.013), but not current depression (OR = 1.1, p = 0.91). Multivariate logistic regression results, adjusting for age, gender, marital status, level of education, current psychotropic medication use, and concussion history, confirmed these results. CONCLUSION: Grapheme-color synesthesia appears to be associated with PTSD among veterans who had been deployed. This finding may have implications for PTSD diagnostic screening and treatment. Research is recommended to confirm this finding and to determine if synesthesia is a risk indicator for PTSD among nonveterans.